Ethyl Oleate Synthesis Using Candida rugosa Lipase in a Solvent-Free System. Role of Hydrophobic Interactions - Trubiano, G. (2004)
The solvent-free esterification reaction of a commercial oleic acid and ethanol was selected as the test reaction for Candida rugosa lipase immobilized on polypropylene (PP) at 318 K (initial molar ratio 1:1). Adding of water from 0 to 30 wt. % (in gram per gram of fatty acid × 100) and the pretreatment of Candida rugosa lipase with polyethylenglycol (PEG), octane, and acetone increases the conversion to ethyl esters. The role of hydrophobic interactions of the lipase with PP and PEG was studied using molecular mechanics (MM2) for calculation of steric energies and the parametrized model (PM3) for calculation of enthalpy changes upon interaction. The nonpolar lateral groups of amino acids interact strongly with PP, whereas polar groups interact more strongly with PEG. Both interactions stabilize the open, active conformation of the lipase from Candida rugosa. Activities ranged from 5 × 10-5 to 2.0 × 10-4 mol ethyl oleate/h/mg enzyme, depending on reaction conditions. Steric energy changes vary between +30 and -10 kcal/mol, whereas the enthalpy changes ranged from +10 to -10 kcal/mol.